Customer retention and cross-buying in premium banking services : the roles of switching costs and interaction quality - Laksamana, Patria (Curtin University, 2012)
The emergence of e-banking and intense competition in premium banking services have essentially evolved the way banks have conventionally conducted their business and the way customers interact with banks. Consequently, banks are increasingly confronted with the conundrum: customers may appreciate the convenience of e-banking but as they migrate away from conventional banking mediums, the extent of personal interaction with bank staff –and in the case of premium banking services their Relationship Managers –decreases as do switching costs and, ultimately, long-term customer commitment.While the constructs of commitment and trust have been widely applied in relationship marketing studies, there is a need for a more comprehensive model and more objective measurement of continuance commitment. In response, based on payment equity theory and social exchange theory, as well as logical arguments from previous research, this thesis extends Morgan and Hunt’s (1994) commitment–trust model into a single model that encompasses moderating effects such as switching costs and interaction quality as well as continuance commitment in the form of retention and cross-buying. It is important to study customer retention and cross-buying simultaneously, as they have been studied separately in previous research. The purpose of the study is thus to examine the roles of switching costs and interaction quality along with other key relational variables that influence customer retention and cross-buying behaviour in the premium banking services sector.Primary data for the study were collected from 525 bank customers in a large metropolitan area in Australia. The study identifies the importance of switching costs and interaction quality and their relationship with trust, reputation and expertise for continuance commitment (retention and cross-buying). Regression analysis and MANOVA were used to test the hypotheses. The analyses of the findings of this thesis provide support to the model and, in the main, support the hypotheses. The results confirm that while reputation and expertise have a positive impact on retention, they do not affect cross-buying. Only trust has a positive impact on both retention and cross-buying. To further investigate the roles of switching costs and interaction quality, investigation was carried out to examine if these two constructs moderate the relationship between trust and continuance commitment (retention and cross-buying). The results confirm that although switching costs have no impact on retention, they do affect cross-buying. Conversely, interaction quality has a positive impact on retention, but no effect on cross-buying. Hence, it can be concluded that customer retention is not necessarily translated into cross-buying.Primary data for the study were collected from 525 bank customers in a large metropolitan area in Australia. The study identifies the importance of switching costs and interaction quality and their relationship with trust, reputation and expertise for continuance commitment (retention and cross-buying). Regression analysis and MANOVA were used to test the hypotheses. The analyses of the findings of this thesis provide support to the model and, in the main, support the hypotheses. The results confirm that while reputation and expertise have a positive impact on retention, they do not affect cross-buying. Only trust has a positive impact on both retention and cross-buying. To further investigate the roles of switching costs and interaction quality, investigation was carried out to examine if these two constructs moderate the relationship between trust and continuance commitment (retention and cross-buying). The results confirm that although switching costs have no impact on retention, they do affect cross-buying. Conversely, interaction quality has a positive impact on retention, but no effect on cross-buying. Hence, it can be concluded that customer retention is not necessarily translated into cross-buying.